Legal Certainty of Sale and Purchase Binding Agreements as the Basis for the Transfer of Certified Land Rights - Chandra, Tofik (Research Horizon, 2022)
In essence, a binding sale and purchase agreement represents a commitment or promise between the seller and buyer prior to the actual transaction. Such agreements typically involve certain conditions or promises that must be fulfilled by one or both parties before the main transaction, i.e., the sale and purchase, can take place. This study explores the legal implications of privately made binding sale and purchase agreements in the transfer of certified land rights. It delves into the legal consequences of these agreements, which, while legally binding, can result in adverse outcomes if either party engages in unethical practices or fraudulent behavior during private land transactions. The involvement of the land deed official (Pejabat Pembuat Akta Tanah or PPAT), a government-appointed official, is crucial to ensure the integrity of the land transfer process. Furthermore, this research addresses the legal certainty of binding sale and purchase agreements made under the hands as a means of transferring certified land rights. It emphasizes that the legal certainty of land transfers through buying and selling is contingent on compliance with PP No. 24 of 1997, which mandates that land transactions can only occur with proof of legal ownership based on the seller's documented land rights.